2021
DOI: 10.1029/2020gc009411
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous Sedimentation in Gonjo Basin, Southeast Tibet in Response to India‐Asia Collision Constrained by Magnetostratigraphy

Abstract: The India-Asia collision has been the object of vigorous debate for decades, with ages of the start ranging from Late Cretaceous to Oligocene. Sedimentary records preserved in both near-field and far-field settings provide critical evidence concerning the age and mechanism of the collision. Gonjo Basin, one of a series of fault-controlled basins developed along the eastern margin of Tibetan Plateau, contains well-exposed sedimentary successions, providing great potential for understanding depositional, tectoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(49 citation statements)
references
References 69 publications
3
45
1
Order By: Relevance
“…These data also indicate that the basin experienced ∼10° counter‐clockwise rotation at 69–67 Ma and ∼30° clockwise rotation at 52–48 Ma, followed by another ∼30° clockwise rotation sometime after 41 Ma. However, recent research using high‐resolution magnetostratigraphy, constrained by zircon U‐Pb dating from volcaniclastic layers shows that sedimentation in the center of the Gonjo Basin started at 69 Ma and continued until 50 Ma (Xiao et al., 2021). Although the exact sedimentary age of the Gonjo Basin is still under debate, the depositional age of the Gonjo Basin coincides with the time of the proposed paleo‐Jinshajiang, but whether it formed part of the paleo‐river system needs further work to verify.…”
Section: Geological Settingmentioning
confidence: 99%
“…These data also indicate that the basin experienced ∼10° counter‐clockwise rotation at 69–67 Ma and ∼30° clockwise rotation at 52–48 Ma, followed by another ∼30° clockwise rotation sometime after 41 Ma. However, recent research using high‐resolution magnetostratigraphy, constrained by zircon U‐Pb dating from volcaniclastic layers shows that sedimentation in the center of the Gonjo Basin started at 69 Ma and continued until 50 Ma (Xiao et al., 2021). Although the exact sedimentary age of the Gonjo Basin is still under debate, the depositional age of the Gonjo Basin coincides with the time of the proposed paleo‐Jinshajiang, but whether it formed part of the paleo‐river system needs further work to verify.…”
Section: Geological Settingmentioning
confidence: 99%
“…The NNW‐SSE orientated Gonjo Basin (Figure 1), has a ∼260 km length, ∼2–16 km width and present‐day mean elevation of ∼4 km (Xiao et al., 2021). The fill of the Gonjo Basin forms an asymmetrical syncline controlled by thrust faults, with thicker sediments in the west compared to the east of the syncline (Li et al., 2020; Xiao et al., 2021; Xiong et al., 2020). The basin is filled with late Cretaceous to early Eocene fluvio‐lacustrine sediments (>2,500 m thickness) (Studnicki‐Gizbert et al., 2008; Xiao et al., 2021).…”
Section: Geological Settingmentioning
confidence: 99%
“…A magnetostratigraphic study in the central part of the basin revealed that the ages of the continuous sequences of the Gonjo and Ranmugou formations ranged from ~69 Ma to 41.5 Ma, of which the Ranmugou Formation is ~65.2 Ma to 41.5 Ma (Li et al, 2020) (Figure 2). Xiao et al (2021) indicated that the Gonjo and Ranmugou formations are 69 to 50 Ma in the central Gonjo Basin, and the Ranmugou Formation was assigned an age ranging between 63.5 Ma and 50 Ma. They believed that the magnetostratigraphic results of Li et al (2020) were inaccurate due to their isotopic age deriving from other sections.…”
Section: Geologic Settingmentioning
confidence: 99%
“…Sparse sporomorphs fossils indicate a wide age range of Paleocene to Oligocene (BGMRT, 1993;Studnicki-Gizbert et al, 2008). The magnetostratigraphy and volcanic U-Pb studies limited the age from 50 to 40 Ma (Xiong et al, 2020) or from 43.4 to 41.5 Ma (Li et al, 2020) or from 54 to 50 Ma (Xiao et al, 2021) for the upper Ranmugou Formation. The palynoflora assemblages in the Youzha section discussed below give an age of middle Eocene, which is congruent with the isotopic ages in the Qudeng section (Xiong et al, 2020).…”
Section: Age Constraintsmentioning
confidence: 99%
See 1 more Smart Citation